Annealing separator composition for grain-oriented electrical steel sheet and method for producing grain-oriented electrical steel sheet

The use of a boron compound-based annealing separator composition with magnesium oxide or hydroxide addresses adhesion and core loss issues in grain-oriented electrical steel sheets, enhancing film tension and insulation, resulting in improved magnetic properties and uniform film formation.

JP2025500961AActive Publication Date: 2025-01-15POHANG IRON & STEEL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024537446
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-20
Filing Date
2022-12-20
Publication Date
2025-01-15
Estimated Expiration
2042-12-20

AI Technical Summary

Technical Problem

Existing grain-oriented electrical steel sheets face challenges in achieving excellent adhesion, film tension, and core loss due to limitations in insulation film formation and poor adhesion of silica films, which are difficult to control during the secondary recrystallization annealing process.

Method used

An annealing separator composition containing 25 to 80% by weight of a boron compound, along with magnesium oxide or magnesium hydroxide, and optionally including metal hydroxides and ceramic powders, is applied to form a film with boron aggregates and a ceramic layer, enhancing film tension and insulation properties.

Benefits of technology

The composition results in grain-oriented electrical steel sheets with improved iron loss, magnetic flux density, and excellent film adhesion and insulation properties, ensuring uniform film formation and stability during high-temperature annealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500961000001_ABST
    Figure 2025500961000001_ABST
Patent Text Reader

Abstract

The present invention provides an annealing separator composition for grain-oriented electrical steel sheet, which has excellent adhesion and film tension and can improve the iron loss of the material, and a method for producing grain-oriented electrical steel sheet. An annealing separator composition for grain-oriented electrical steel sheet according to one embodiment of the present invention contains, based on 100% by weight of total solids, 25 to 80% by weight of a boron compound, and the remainder being one or more of magnesium oxide and magnesium hydroxide.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] An embodiment of the present invention relates to an annealing separator composition for grain-oriented electrical steel sheet and a method for producing grain-oriented electrical steel sheet, more specifically, to an annealing separator composition for grain-oriented electrical steel sheet containing a boron compound and a method for producing grain-oriented electrical steel sheet. [Background technology]

[0002] Generally, grain-oriented electrical steel is a steel sheet containing silicon and has a grain orientation of {110} <001> This refers to electrical steel sheet that has a texture aligned in the rolling direction and has extremely excellent magnetic properties in the rolling direction. In the case of commonly known grain-oriented electrical steel sheets, an insulating film is formed on a forsterite (Mg2SiO4)-based base film, and tensile stress is applied to the steel sheet by utilizing the difference in the thermal expansion coefficient of the insulating film, thereby improving iron loss and reducing noise caused by magnetic deformation. However, there is a limit to how much this can satisfy the characteristic levels required for high-grade grain-oriented electrical steel sheets recently.

[0003] In the conventional manufacturing process of grain-oriented electrical steel sheets, a method has been proposed in which an anti-adhesive agent mainly composed of MgO is applied in order to improve the properties of the forsterite film, and in this step, TiO2 powder is added to the MgO to improve the surface properties. In addition, to improve the film tension compared to conventional forsterite, kaolinite (Al4Si4O 10 A method has been proposed in which a composite coating consisting of alumina and silica is formed on the surface of a steel sheet by applying oxidized kaolinite as an annealing separator and then performing finish annealing. However, this method is a technology for forming a composite coating with a double structure consisting of alumina on the top and silica on the bottom by decomposing kaolinite, and it is difficult to control the secondary recrystallization annealing process, making it difficult to form a uniform quality, and there are problems with poor adhesion due to the silica coating formed on the bottom.

[0004] As a method for improving the iron loss of grain-oriented electrical steel sheets, a method is known in which alumina powder or a mixture of colloidal silica and MgCl2 is applied as an anti-adhesion agent to remove the forsterite film. However, this method has the problem that removing the forsterite film actually worsens the iron loss of the electrical steel sheet, and there is also the problem that it is difficult to form an insulating film in a post-process. Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide an annealing separator composition for grain-oriented electrical steel sheets and a method for producing grain-oriented electrical steel sheets. Specifically, it is an object of the present invention to provide an annealing separator composition for grain-oriented electrical steel sheets and a method for producing grain-oriented electrical steel sheets that are excellent in adhesion and film tension and can improve the iron loss of the material. [Means for solving the problem]

[0006] An annealing separator composition for grain-oriented electrical steel sheet according to one embodiment of the present invention is characterized in that it contains, based on 100% by weight of total solids, 25 to 80% by weight of a boron compound, and the remainder being one or more of magnesium oxide and magnesium hydroxide.

[0007] Boron compounds include BBr3, BCl3, BF, BF3, BI3, BN, B(NO3)3, B(OH)3, BP, BPO4, B2F4, B2Cl4, B2H6, BH3NH3, B2O, B2O3, B2S3, B4C, B6O, B5H9, B5H 11 , B6H 10 , B6H 12 , LiBH4, H3BO3, Na2B4O7, H2B4O7, B2O3, B2O, B2C, MgB2, H[B(OH)4], H[BF(OH)3], H[BF2(OH)2], H[BF3(OH)] and H[BF4].

[0008] The annealing separator composition for grain-oriented electrical steel sheet according to an embodiment of the present invention may further contain 0.1 to 20 wt % of a metal hydroxide.

[0009] The metal hydroxides can include one or more of Ni(OH)2, Co(OH)2, Cu(OH)2, Sr(OH)2, Ba(OH)2, Pd(OH)2, In(OH)3, Bi(OH)3, and Sn(OH).

[0010] The annealing separator composition for grain-oriented electrical steel sheet according to an embodiment of the present invention may further include 0.5 to 10 wt % of ceramic powder.

[0011] The ceramic powder may include one or more of MnO, Al2O3, SiO2, TiO2, and ZrO.

[0012] The annealing separator composition for grain-oriented electrical steel sheet according to an embodiment of the present invention may further contain 1 to 10 wt % of one or more of Sb2(SO4)3, SrSO4, and BaSO4.

[0013] According to an embodiment of the present invention, a grain-oriented electrical steel sheet includes a grain-oriented electrical steel sheet substrate and a coating that is disposed on one or both sides of the grain-oriented electrical steel sheet substrate and contains boron and forsterite. The coating may contain boron aggregates, and the average particle size of the boron aggregates may be 1 to 500 nm.

[0014] The coating may contain boron aggregates in an amount of 1 to 45% by area based on the total area of ​​the coating.

[0015] The coating may contain 1 to 40 wt % B, 10 to 70 wt % Mg, 3 to 70 wt % Si, 10 to 90 wt % O, and the balance Fe.

[0016] The grain-oriented electrical steel sheet according to an embodiment of the present invention may further include a ceramic layer disposed on the coating.

[0017] The ceramic layer may include a ceramic powder and a metal phosphate.

[0018] The ceramic powder may include one or more selected from Al2O3, SiO2, TiO2, ZrO2, Al2O3·TiO2, Y2O3, 9Al2O3·2B2O3, BN, CrN, BaTiO3, SiC, and TiC.

[0019] A method for manufacturing a grain-oriented electrical steel sheet according to an embodiment of the present invention includes the steps of: preparing a steel slab; hot rolling the steel slab to manufacture a hot-rolled sheet; cold rolling the hot-rolled sheet to manufacture a cold-rolled sheet; performing a primary recrystallization annealing on the cold-rolled sheet; applying an annealing separator to a surface of the steel sheet that has been subjected to the primary recrystallization annealing; and performing a secondary recrystallization annealing on the steel sheet to which the annealing separator has been applied. The annealing separator is characterized in that it contains 25 to 80% by weight of a boron compound based on 100% by weight of total solids, and at least one of magnesium oxide and magnesium hydroxide as the balance.

[0020] The method may further include forming a ceramic layer on the coating containing boron and forsterite after the step of secondary recrystallization annealing. The coating containing boron and forsterite may include 1 to 40 wt% B, 10 to 70 wt% Mg, 3 to 70 wt% Si, 10 to 90 wt% O, and the balance Fe.

[0021] The step of forming the ceramic layer may include spraying ceramic powder onto the coating to form the ceramic layer. The step of forming the ceramic layer may be a step of applying a ceramic layer-forming composition containing a ceramic powder and a metal phosphate onto the coating to form the ceramic layer. The ceramic powder used in the step of forming the ceramic layer may include one or more selected from Al2O3, SiO2, TiO2, ZrO2, Al2O3·TiO2, Y2O3, 9Al2O3·2B2O3, BN, CrN, BaTiO3, SiC and TiC.

[0022] The step of subjecting the cold-rolled sheet to primary recrystallization annealing may include the steps of simultaneously subjecting the cold-rolled sheet to decarburization annealing and nitriding annealing, or may include the steps of subjecting the cold-rolled sheet to decarburization annealing followed by nitriding annealing. Effect of the Invention

[0023] According to one embodiment of the present invention, it is possible to provide a grain-oriented electrical steel sheet having excellent core loss and magnetic flux density, and excellent coating adhesion and insulation, and a method for producing the same. [Brief description of the drawings]

[0024] [Figure 1] 1 is a schematic cross-sectional side view of a grain-oriented electrical steel sheet according to an embodiment of the present invention; [Diagram 2] 1 is a scanning electron microscope (SEM) photograph of the coating of the grain-oriented electrical steel sheet produced in Example 9. [Diagram 3] 1 is a scanning electron microscope (SEM) photograph of a coating of the grain-oriented electrical steel sheet produced in Comparative Example 2. [Figure 4] 1 shows the results of an EPMA (Electron Probe Micro-Analyzer) analysis of B element in the coating of the grain-oriented electrical steel sheet produced in Example 3. [Diagram 5] 1 shows the results of an EPMA (Electron Probe Micro-Analyzer) analysis of B element in the coating of the grain-oriented electrical steel sheet produced in Example 6. [Figure 6] 1 shows the results of an EPMA (Electron Probe Micro-Analyzer) analysis of B element in the coating of the grain-oriented electrical steel sheet produced in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Terms such as first, second and third are used to describe various parts, components, regions, layers and / or sections, but are not limited thereto. These terms are used only to distinguish one part, component, region, layer or section from another part, component, region, layer or section. Thus, a first part, component, region, layer or section described below can be referred to as a second part, component, region, layer or section without departing from the scope of the present invention.

[0026] The terminology used herein is merely for the purpose of referring to specific embodiments and is not intended to limit the present invention. As used herein, the singular form includes the plural form unless the text clearly indicates otherwise. As used herein, the meaning of "comprises" is intended to embody certain properties, regions, integers, steps, operations, elements and / or components, and does not exclude the presence or addition of other properties, regions, integers, steps, operations, elements and / or components.

[0027] When an element is described as being "on" or "above" another element, it may be exactly on or above the other element, or it may have other elements between them. In contrast, when an element is described as being "directly on" another element, there are no other elements between them.

[0028] In the present invention, 1 ppm means 0.0001%. In one embodiment of the present invention, the term "further comprising an additional component" means that an additional amount of the additional component is substituted for the remainder. Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. Terms defined in commonly used dictionaries are interpreted as having a meaning consistent with the relevant technical literature and the presently disclosed content, and are not interpreted as having an ideal or extreme meaning unless otherwise defined.

[0029] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a schematic diagram of a method for manufacturing a semiconductor device according to the present invention;

[0030] The annealing separator composition for grain-oriented electrical steel sheet according to one embodiment of the present invention contains, based on the solid content, 25 to 80% by weight of a boron compound, and the remainder being one or more of magnesium oxide and magnesium hydroxide, where the solid content based means that the solid content excluding volatile components such as solvents is set to 100% by weight.

[0031] Hereinafter, the annealing separator composition according to an embodiment of the present invention will be described in detail with respect to each component. The annealing separator composition according to one embodiment of the present invention is applied to a grain-oriented electrical steel substrate 10 to form a coating 20 containing boron and forsterite. Boron has a small thermal expansion coefficient (5×10 -6 / ℃), and it is easy to improve core loss by applying tension to the film. In addition, boron has a relatively low elastic modulus, so it has excellent thermal shock resistance.

[0032] The existing forsterite (Mg2SiO4) film of the primary film is formed by a chemical reaction between the internal oxide layer (SiO2) present on the steel sheet surface and magnesium oxide (MgO) in the annealing separator during secondary recrystallization annealing. Although the conventional forsterite film has excellent functionality in preventing sheet sticking due to contact between coils during the secondary recrystallization annealing process, it has limitations such as poor film tensioning ability and insulation properties.

[0033] In one embodiment of the present invention, the film tensioning ability and insulating properties can be dramatically improved by adding a boron compound in addition to magnesium oxide or magnesium hydroxide. However, when a boron compound is used alone as an annealing separator, there is a problem that the film peels off due to a significant difference in thermal expansion coefficient during the secondary recrystallization annealing process. In addition, when used as an annealing separator, the boron component has a high specific gravity and sinks without being dispersed in the solvent, making it difficult to apply it uniformly to the surface of the electrical steel sheet. In one embodiment of the present invention, boron is not used alone but is mixed with magnesium oxide or magnesium hydroxide.

[0034] Kaolinite (Al4Si4O 10 When (OH)8) is used as an annealing separator, it is difficult to control the secondary recrystallization annealing process, making it difficult to form uniform quality, and there is a problem that adhesion is poor due to the silica film formed on the bottom due to the decomposition of kaolinite. In one embodiment of the present invention, the annealing separator composition contains 25 to 80 wt % of a boron compound based on the solid content. If the boron compound is contained in a small amount, the formation of a forsterite film may be insufficient, resulting in poor adhesion. In addition, the film tension imparting ability and the improvement of insulating properties may be insufficient. If the boron compound is contained in too much amount, a problem may occur in uniformly applying the annealing separator. Therefore, the boron compound may be contained within the above-mentioned content range. More specifically, the boron compound may be contained in 30 to 70 wt %.

[0035] Boron compounds can exist in various forms, specifically, chlorides, oxides, nitrates, sulfides, etc., and more specifically, BBr3, BCl3, BF, BF3, BI3, BN, B(NO3)3, B(OH)3, BP, BPO4, B2F4, B2Cl4, B2H6, BH3NH3, BO, BO3, BS3, BC, BO, B5H9, B5H 11 , B6H 10 , B6H 12, LiBH4, H3BO3, Na2B4O7, H2B4O7, B2O3, B2O, B2C, MgB2, H[B(OH)4], H[BF(OH)3], H[BF2(OH)2], H[BF3(OH)] and H[BF4]. When two or more boron compounds are contained, the total amount is 25 to 80% by weight.

[0036] In one embodiment of the present invention, the annealing separator composition may contain 5 to 600 parts by weight of a boron compound with respect to 100 parts by weight of at least one of magnesium oxide and magnesium hydroxide based on the solid content mass. Specifically, the boron compound may be contained in an amount of 10 to 500 parts by weight, more specifically, in an amount of 50 to 300 parts by weight. If the content of boron is too low compared to magnesium oxide or magnesium hydroxide, the formation of a forsterite film may be insufficient, and the adhesion may be poor. In addition, the film tension imparting ability and the insulating property imparting ability may be insufficient, and if the content is too high, the function of the annealing separator may be deteriorated, and a sheet-to-sheet sticking phenomenon may occur during high-temperature annealing.

[0037] Metal hydroxide plays a role in changing the surface properties of boron compounds from hydrophobic to hydrophilic through chemical reaction with the surface. This dramatically improves the dispersibility of boron compounds and helps to form a uniform forsterite film. In addition, metal hydroxide lowers the melting point, lowering the film formation temperature in the secondary recrystallization annealing process and ensuring good quality surface properties. In addition, the forsterite film formed at a low temperature range has the effect of suppressing the decomposition of AlN-based inhibitors, which have a decisive effect on the formation of secondary recrystallization, ensuring excellent magnetic quality.

[0038] In one embodiment of the present invention, the annealing separator composition may further contain 0.1 to 20 wt % of metal hydroxide. If the metal hydroxide content is too low, there may be a problem in fully exhibiting the above-mentioned effects. If the metal hydroxide content is too high, there may be a problem in that the metal component diffuses inside and forms a film, resulting in non-uniform forsterite formation behavior. When the annealing separator further contains additional components, they may be contained in place of the remaining magnesium oxide and magnesium hydroxide. Here, the metal hydroxide refers to a metal hydroxide other than magnesium hydroxide described above. Specifically, the metal hydroxide may include one or more selected from Cr(OH)3, Ni(OH)2, Co(OH)2, Cu(OH)2, Sr(OH)2, Ba(OH)2, Pd(OH)2, In(OH)3, Bi(OH)3, and Sn(OH). Magnesium oxide (MgO) and magnesium hydroxide (Mg(OH)2) serve to supply Mg to the coating. In one embodiment of the present invention, the annealing separator composition may be present in the form of a slurry so as to be easily applied to the surface of the grain-oriented electrical steel sheet substrate. When the slurry contains water as a solvent, magnesium oxide is easily dissolved in water and may be present in the form of magnesium hydroxide. Therefore, in one embodiment of the present invention, magnesium oxide and magnesium hydroxide are treated as one component.

[0039] The annealing separator composition according to an embodiment of the present invention may further include 0.5 to 10 wt % of ceramic powder. The ceramic powder may include one or more selected from MnO, Al2O3, SiO2, TiO2, and ZrO. When an appropriate amount of ceramic powder is further included, the insulating properties of the formed coating 20 can be further improved.

[0040] The annealing separator composition according to an embodiment of the present invention may further contain 1 to 10 wt % of Sb2(SO4)3, SrSO4, BaSO4 or a combination thereof. By further containing an appropriate amount of Sb2(SO4)3, SrSO4, BaSO4 or a combination thereof, it is possible to produce a grain-oriented electrical steel sheet having excellent surface gloss and beautiful roughness. The annealing separator composition may further contain a solvent for uniform dispersion of the solid matter and easy application. As the solvent, water, alcohol, etc. may be used, and the solvent may be contained in an amount of 300 to 1000 parts by weight per 100 parts by weight of the solid matter. In this way, the annealing separator composition may be in the form of a slurry.

[0041] In the grain-oriented electrical steel sheet 100 according to an embodiment of the present invention, a coating 20 containing boron and forsterite is formed on one or both sides of a grain-oriented electrical steel sheet substrate 10. Fig. 1 shows a schematic side cross-sectional view of a grain-oriented electrical steel sheet according to an embodiment of the present invention. Fig. 1 shows a case where the coating 20 is formed on the upper surface of the grain-oriented electrical steel sheet substrate 10. The coating 20 containing boron and forsterite has superior coating tension imparting ability and insulating properties compared to conventional forsterite coatings, and its melting point is lowered, lowering the temperature at which the coating 20 is formed during the secondary recrystallization annealing process, ensuring good quality surface characteristics. In addition, the coating 20 formed in a low temperature range has the effect of suppressing the decomposition of AlN-based inhibitors, which have a decisive effect on the formation of secondary recrystallization, ensuring excellent magnetic quality. This has been described above, so a repeated explanation will be omitted.

[0042] The coating 20 may contain 1-40% by weight of B, 10-70% by weight of Mg, 3-70% by weight of Si, 10-90% by weight of O, and the remainder being Fe. The elemental composition of Mg, Si, and Fe originates from diffusion from the steel sheet and from the annealing separator components. In the case of O, it originates from the annealing separator components, or it may penetrate during the heat treatment process. In addition, it may further contain impurity components such as carbon (C). In the case of B, it originates from the annealing separator components, and by containing B in the above range in the coating 20, the coating tension imparting ability and insulating properties are improved.

[0043] In one embodiment of the present invention, the element contents in the coating may vary depending on the measurement position, and the above-mentioned element ranges refer to the average element contents in the coating 20. More specifically, the coating may contain 1.0 to 40.0 wt % B, 15.0 to 50.0 wt % Mg, 10.0 to 30.0 wt % Si, 20.0 to 50.0 wt % O, and Fe as the balance.

[0044] In the film 20, B is BBr3, BCl3, BF, BF3, BI3, BN, B(NO3)3, B(OH)3, BP, BPO4, B2F4, B2Cl4, B2H6, BH3NH3, B2O, B2O3, B2S3, B4C, B6O, B5H9, B5H 11 , B6H 10 , B6H 12 , LiBH4, H3BO3, Na2B4O7, H2B4O7, B2O3, B2O, B2C, MgB2, H[B(OH)4], H[BF(OH)3], H[BF2(OH)2], H[BF3(OH)], etc. In particular, it can be present in the form of boron aggregates such as borosilicate, magnesium borate, boroaluminosilicate, or a composite thereof. When boron aggregates are present in the coating 20, the coating tension imparting ability and insulating properties are improved. In order to appropriately impart the coating tension and improve the insulating properties, the average particle size of the boron aggregates may be 1 to 500 nm. In this case, the average particle size means the number average particle size of the boron aggregates when the surface of the coating 20 is observed over an area of ​​400 μm x 400 μm or more using EPMA (Electron Probe X-ray Micro Analyzer), which is a non-destructive fragmentation method. The particle size means the circle equivalent diameter of the boron aggregates. The boron aggregates refer to aggregates in which B aggregates to the base level or above of the coating 20 and aggregates in the form of a particle size of 1 nm or more. More specifically, the average particle size of the boron aggregates may be 3 to 500 nm. More specifically, the average particle size of the boron aggregates may be 10 to 200 nm. Furthermore, the boron aggregates may occupy 1 to 45 area % of the coating 20. More specifically, they may occupy 2 to 35 area %.

[0045] The coating 20 may have a thickness of 0.1 to 10 μm. If the coating 20 is too thin, the coating tension imparting ability may decrease, and problems such as poor core loss may occur. If the coating 20 is too thick, problems such as poor drip rate and poor transformer characteristics may occur. Therefore, the thickness of the forsterite coating 20 may be adjusted to the above-mentioned range. More specifically, the thickness of the forsterite coating 20 may be 0.8 to 6 μm. The boundary between the coating 20 and the steel sheet substrate 10 may be divided into a coating 20 containing 5 wt % or more of Mg and a portion containing less than 5 wt % of Mg in the thickness direction of the steel sheet. Even when a ceramic layer 30 is further formed on the coating 20, it may be divided into a coating 20 containing 5 wt % or more of Mg and a ceramic layer 30 containing less than 5 wt % of Mg, based on 5 wt % of Mg.

[0046] In the grain-oriented electrical steel sheet 100 according to an embodiment of the present invention, a ceramic layer 30 may be further formed on the coating 20. FIG. 1 shows an example in which a ceramic layer 30 is further formed on the coating 20.

[0047] The thickness of the ceramic layer 30 may be 0.5 to 5 μm. If the thickness of the ceramic layer 30 is too thin, a problem may occur in that the insulating effect of the ceramic layer 30 becomes small. If the thickness of the ceramic layer 30 is too thick, the adhesion of the ceramic layer 30 becomes low, and peeling may occur. Therefore, the thickness of the ceramic layer 30 may be adjusted to the above-mentioned range. More specifically, the thickness of the ceramic layer 30 may be 0.8 to 3.2 μm.

[0048] The ceramic layer 30 may include ceramic powder. The ceramic powder may be one or more selected from Al2O3, SiO2, TiO2, ZrO2, Al2O3·TiO2, Y2O3, 9Al2O3·2B2O3, BN, CrN, BaTiO3, SiC, and TiC. The particle size of the ceramic powder may be 2 to 900 nm. If the particle size of the ceramic powder is too small, it may be difficult to form the ceramic layer. If the particle size of the ceramic powder is too large, the surface roughness may become rough and surface defects may occur. Therefore, the particle size of the ceramic powder may be adjusted to the above-mentioned range. The ceramic powder may have one or more shapes selected from the group including spherical, platelet, and needle shapes.

[0049] The ceramic layer 30 may further include a metal phosphate. The metal phosphate may include one or more selected from Mg, Ca, Ba, Sr, Zn, Al, and Mn. When the ceramic layer 30 further includes a metal phosphate, the insulating properties of the ceramic layer 30 are further improved. The metal phosphate may be a compound formed by a chemical reaction between a metal hydroxide and phosphoric acid (H3PO4). Metal phosphates are compounds formed by the chemical reaction of a metal hydroxide and phosphoric acid (H3PO4), and the metal hydroxide may be at least one selected from the group including Ca(OH)2, Al(OH)3, Mg(OH)2, B(OH)3, Co(OH)2, and Cr(OH)3.

[0050] Specifically, the metal atom of the metal hydroxide may be formed by substitution reaction with phosphorus of the phosphoric acid to form a single bond, a double bond, or a triple bond, and may be composed of a compound having an amount of unreacted free phosphoric acid (H3PO4) of 25 wt% or less. Metal phosphates are compounds formed by a chemical reaction between metal hydroxides and phosphoric acid (H3PO4), and the weight ratio of metal hydroxide to phosphoric acid may be expressed as 1:100 to 40:100. If the metal hydroxide is contained in an excessive amount, a problem may occur in which the chemical reaction is not completed and precipitates are generated, whereas if the metal hydroxide is contained in an excessively small amount, a problem may occur in which the corrosion resistance is deteriorated. Therefore, the range can be limited as described above.

[0051] In one embodiment of the present invention, the effects of the annealing separator composition and coating 20 are achieved regardless of the composition of the grain-oriented electrical steel sheet substrate 10. The composition of the grain-oriented electrical steel sheet substrate 10 will be additionally described as follows. The grain-oriented electrical steel sheet substrate 10 contains 2.8 to 4.5 weight percent silicon (Si), 0.020 to 0.040 weight percent aluminum (Al), 0.01 to 0.20 weight percent manganese (Mn), and 0.01 to 0.15 weight percent of antimony (Sb), tin (Sn), nickel (Ni) or a combination thereof, with the remainder containing Fe and other unavoidable impurities. The reasons for limiting the components of the grain-oriented electrical steel sheet substrate 10 will be explained below.

[0052] Si:2.8~4.5wt% Silicon (Si) plays a role in increasing the resistivity of steel and reducing iron loss, but if the Si content is too low, the resistivity of the steel decreases, the iron loss characteristics deteriorate, and there is a phase transformation region during high-temperature annealing, which may cause problems with unstable secondary recrystallization. If the Si content is too high, there may be problems with increased brittleness and difficulty in cold rolling. Therefore, the Si content can be adjusted to within the above range. More specifically, Si can be included in an amount of 3.0 to 4.0 wt%.

[0053] Al:0.020~0.040wt% Aluminum (Al) is a component that ultimately becomes nitrides of the type AlN, (Al,Si)N, and (Al,Si,Mn)N, and acts as an inhibitor. If the Al content is too low, sufficient inhibitory effect cannot be expected. Also, if the Al content is too high, Al-based nitrides precipitate and grow coarsely, which may result in insufficient inhibitory effect. Therefore, the Al content can be adjusted to the above-mentioned range.

[0054] Mn:0.01~0.20wt% Manganese (Mn), like Si, has the effect of increasing resistivity and reducing iron loss, and is an important element for suppressing the growth of primary recrystallization grains and causing secondary recrystallization by reacting with nitrogen introduced by nitriding together with Si to form precipitates of (Al, Si, Mn)N. However, if the Mn content is too high, it promotes austenite phase transformation during hot rolling, reducing the size of primary recrystallization grains and making secondary recrystallization unstable. Also, if the Mn content is too low, the effect of increasing the austenite fraction during hot rolling reheating, increasing the high capacity of precipitates, and preventing primary recrystallization grains from becoming excessively large due to refinement of precipitates and formation of MnS during reprecipitation may be insufficient. Therefore, the Mn content can be adjusted to the above range.

[0055] Sb, Sn, Ni or a combination thereof: 0.01 to 0.15% by weight Antimony (Sb), tin (Sn), and nickel (Ni) are grain segregation elements that hinder the movement of grains, so they are used as grain growth inhibitors. <001> It is an important element for controlling grain size because it promotes the generation of Goss grains in the orientation and allows secondary recrystallization to develop well. If the content of Sb, Sn, or Ni added alone or in combination is too small, there is a possibility that the effect of the element is reduced. If the content of Sb, Sn, or Ni added alone or in combination is too high, there is a possibility that grain segregation becomes severe, the brittleness of the steel sheet increases, and sheet breakage may occur during rolling. More specifically, Sb may be contained at 0.01 to 0.05 wt%, Sn at 0.01 to 0.12 wt%, and Ni at 0.01 to 0.06 wt%.

[0056] C: 0.01% by weight or less In the embodiment of the present invention, C is an ingredient that is not significantly useful for improving the magnetic properties of the grain-oriented electrical steel sheet, and therefore it is preferable to remove it if possible. However, if it is contained at a certain level or more, it has the effect of promoting the austenite transformation of the steel during the rolling process, refining the hot-rolled structure during hot rolling, and helping to form a uniform fine structure, so that the C content in the slab is preferably 0.03 wt% or more. However, if the C content is excessive, coarse carbides are formed and are difficult to remove during decarburization, so it is preferable that the C content is 0.08 wt% or less. In the manufacturing process of grain-oriented electrical steel sheet, carbon is decarburized through the decarburization annealing process, and the C content in the finally manufactured grain-oriented electrical steel sheet is 0.01 wt% or less.

[0057] N:0.005~0.05wt% N is an element that reacts with Al and the like to refine the crystal grains. When these elements are appropriately distributed, as described above, it is useful for properly refining the structure after cold rolling and ensuring an appropriate primary recrystallization grain size. However, if the content is excessive, the primary recrystallization grains are excessively refined, and as a result, the driving force for grain growth during secondary recrystallization due to the fine crystal grains increases, and crystal grains of undesirable orientation may grow. In addition, if the N content is excessive, it is undesirable because it takes a lot of time to remove it during the final annealing process. Therefore, the upper limit of the nitrogen content in the slab is 0.005 wt%, and since the content of nitrogen employed during slab reheating must be 0.001 wt% or more, it is preferable that the lower limit of the nitrogen content in the slab is 0.001 wt%. In the manufacturing process of grain-oriented electrical steel sheet, nitrogen is partially penetrated through the immersion annealing process, and the grain-oriented electrical steel sheet finally manufactured contains 0.005 to 0.05 wt% of N.

[0058] A method for manufacturing a grain-oriented electrical steel sheet according to an embodiment of the present invention includes the steps of preparing a steel slab (S10), hot rolling the steel slab to manufacture a hot-rolled sheet (S20), cold rolling the hot-rolled sheet to manufacture a cold-rolled sheet (S30), performing a first recrystallization annealing on the cold-rolled sheet (S40), applying an annealing separator to the surface of the steel sheet that has been first recrystallization annealed (S50), and performing a second recrystallization annealing on the steel sheet to which the annealing separator has been applied (S60). In addition, the method for manufacturing a grain-oriented electrical steel sheet may further include other steps.

[0059] First, in step (S10), a steel slab is prepared. The components of the steel slab have been specifically explained for the grain-oriented electrical steel sheet, so a repeated explanation will be omitted. Next, the steel slab can be heated. At this time, the slab can be heated by a low-temperature slab method at a temperature of 1,200°C or less. Next, in step (S20), the heated steel slab is hot rolled to produce a hot-rolled sheet. After step (S20O), the produced hot-rolled sheet can be hot-rolled annealed. Next, in step (S30), the hot-rolled sheet is cold-rolled to produce a cold-rolled sheet. In step (S30), cold rolling can be performed once, or two or more cold rolling steps including intermediate annealing can be performed.

[0060] Next, in step (S40), the cold-rolled sheet is subjected to primary recrystallization annealing. At this time, the step of primary recrystallization annealing the cold-rolled sheet may include a step of simultaneously performing decarburization annealing and nitriding annealing on the cold-rolled sheet, or a step of performing nitriding annealing after decarburization annealing. Next, in step (S50), an annealing separator is applied onto the surface of the steel sheet that has been subjected to the primary recrystallization annealing. The annealing separator has been specifically described above, so a repeated description will be omitted. The amount of the annealing separator applied is 1 to 20 g / m 2 If the amount of the annealing separator applied is too small, the film formation may not be performed smoothly. If the amount of the annealing separator applied is too large, it may affect the secondary recrystallization. Therefore, the amount of the annealing separator applied can be adjusted to the above-mentioned range. Next, in step (S60), the steel sheet coated with the annealing separator is subjected to secondary recrystallization annealing. In the process of secondary recrystallization annealing, a coating 20 containing boron and forsterite is formed.

[0061] During the secondary recrystallization annealing, the primary crack temperature can be 650-750°C, and the secondary crack temperature can be 1100-1250°C. The temperature range of the temperature rise section can be controlled under the condition of 15°C / hr. In addition, the gas atmosphere can be an atmosphere containing 220-30 volume % nitrogen and 70-80 volume % hydrogen up to the primary crack step, and a 100% hydrogen atmosphere can be maintained for 15 hours for the secondary crack step, followed by furnace cooling. The above conditions allow the coating 20 to be formed smoothly.

[0062] After step S60, the method may further include a step of forming the ceramic layer 30. The ceramic layer 30 has been described in detail above, and therefore will not be described again. As a method of forming the ceramic layer 30, a ceramic powder may be sprayed onto the coating 20 to form a ceramic layer. Specifically, plasma spray coating, high velocity oxy fuel, aerosol deposition, and cold spray coating may be used. More specifically, a plasma spray coating method may be used in which a ceramic powder is supplied to a heat source that converts a gas containing Ar, H2, N2, or He into plasma at an output of 20 to 300 kW to form a ceramic layer. In addition, as the plasma spray coating method, a mixture of ceramic powder and a solvent may be supplied in the form of a suspension to a heat source that converts a gas containing Ar, H2, N2, or He into plasma at an output of 20 to 300 kW to form the ceramic layer 30. In this case, the solvent may be water or alcohol.

[0063] Also, a method of forming a ceramic layer by applying a ceramic layer-forming composition containing a ceramic powder and a metal phosphate can be used as a method of forming the ceramic layer 30. After the ceramic layer 30 is formed, magnetic domain refinement can be performed as necessary.

[0064] The present invention will be described in more detail with reference to the following examples. However, these examples are merely for the purpose of illustrating the present invention, and the present invention is not limited thereto.

[0065] Experimental Example 1: Characteristics of Annealing Separator Components and Ceramic Layer Components Example 1 A slab was prepared containing 3.4 wt% silicon (Si), 0.03 wt% aluminum (Al), 0.05 wt% manganese (Mn), 0.04 wt% antimony (Sb), 0.09 wt% tin (Sn), 0.02 wt% nickel (Ni), 0.06 wt% carbon (C), 40 ppm nitrogen (N), and the remainder being Fe and its unavoidable impurities. The slab was heated at 1150°C for 220 minutes and then hot rolled to a thickness of 2.3 mm to produce a hot-rolled sheet.

[0066] The hot-rolled sheet was heated to 1120°C, maintained at 920°C for 95 seconds, quenched in water, pickled, and then cold-rolled to a thickness of 0.23 mm to produce a cold-rolled sheet. The cold-rolled sheet was placed in a furnace maintained at 850°C and then maintained in a mixed atmosphere of 74 vol% hydrogen, 25 vol% nitrogen, and 1 vol% dry ammonia gas for 180 seconds, thereby simultaneously carrying out decarburization soaking and primary recrystallization annealing, thereby producing a steel sheet that had been primary recrystallization annealed. The annealing separator composition was prepared by mixing 30 wt% boron compound (BN), 3 wt% cobalt hydroxide (Co(OH)2), 5 wt% titanium oxide, 35 wt% Sb2(SO4) and the remainder magnesium oxide (MgO) with distilled water to prepare a slurry. The slurry was applied to the steel sheet that had been subjected to the first recrystallization annealing using a roll, and then the steel sheet was subjected to the second recrystallization annealing.

[0067] During secondary recrystallization annealing, the primary crack temperature was 700°C, the secondary crack temperature was 1200°C, and the temperature range in the heating section was 15°C / hr. In addition, up to 1200°C, a mixed gas atmosphere of 50 volume % nitrogen and 50 volume % hydrogen was used, and after reaching 1200°C, a 100 volume % hydrogen gas atmosphere was used for 20 hours, followed by furnace cooling. Then, TiO2 was supplied as ceramic powder to a heat source in which argon (Ar) gas was turned into plasma at an output of 250 kW, and a ceramic layer with a thickness of 0.9 μm was formed on the surface of the final annealed sheet.

[0068] Examples 2 to 8 The same procedure as in Example 1 was carried out, but the boron compound and metal hydroxide components in the annealing separator were changed as shown in Table 1 below to form a coating. In addition, powders of the ceramic layer components summarized in Table 1 below were supplied to the surface of the formed boron-containing forsterite coating to form a ceramic layer.

[0069] Example 9 The same procedure as in Example 1 was carried out, but the boron compound and metal hydroxide components were alternated as shown in Table 1 to form a coating, and no ceramic layer was formed.

[0070] Example 10 The same procedure as in Example 1 was repeated, except that a coating was formed using an annealing separator composition containing 25% by weight of a boron compound, 65% by weight of magnesium oxide, 5% by weight of titanium oxide, and 35% by weight of Sb2(SO4), and no ceramic layer was formed.

[0071] Comparative Example 1 The procedure was the same as in Example 1, but with the use of an annealing separator composition containing 90% by weight of magnesium oxide, 5% by weight of titanium oxide and 35% by weight of Sb2(SO4).

[0072] Comparative Example 2 The same procedure as in Example 1 was carried out, but an annealing separator composition containing 100% by weight of a boron compound was used.

[0073] Comparative Example 3 The same procedure as in Example 1 was carried out, but an annealing separator composition containing 90% by weight of a boron compound, 5% by weight of titanium oxide and 35% by weight of Sb2(SO4) was used.

[0074] Comparative Example 4 The same procedure as in Example 1 was carried out, but an annealing separator composition was used which contained 15% by weight of a boron compound, 5% by weight of titanium oxide, 35% by weight of Sb2(SO4) and 75% by weight of magnesium oxide.

[0075] Comparative Example 5 The procedure was the same as in Example 1, but an annealing separator composition was used containing 15% by weight of a boron compound, 5% by weight of titanium oxide, 10% by weight of aluminum hydroxide and 70% by weight of magnesium oxide. The element contents in the forsterite film of the grain-oriented electrical steel sheets manufactured in the examples and comparative examples were analyzed by a non-destructive fractionation method, EPMA (Electron Probe X-ray Micro Analyzer). The boron aggregates in the forsterite film of the grain-oriented electrical steel sheets manufactured in the Examples and Comparative Examples were analyzed by removing the ceramic layer when it was formed, and observing the surface of the forsterite film in an area of ​​400 μm × 400 μm using an Electron Probe X-ray Micro Analyzer (EPMA). The magnetic properties of the grain-oriented electrical steel sheets produced in the examples and comparative examples were evaluated under conditions of 1.7 T and 50 Hz.

[0076] W17 / 50 means the power loss (W / kg) that occurs when a magnetic field of 50Hz frequency is magnetized with AC up to 1.7 Tesla. Here, Tesla is a unit of magnetic flux density, which means magnetic flux per unit area. B8 indicates the magnetic flux density value (Tesla) that flows through the electrical steel sheet when a current of 800A / m flows through the winding wound around the electrical steel sheet. In addition, the insulating properties were measured on the top of the coating using a Franklin measuring instrument based on the ASTM A717 international standard. The adhesion was expressed as the minimum arc diameter at which the coating did not peel off when the test piece was bent 180° in contact with an arc of 10 to 100 mm. The surface characteristics were evaluated by visually assessing the degree to which a uniform coating was formed and the color was uniform.

[0077] [Table 1]

[0078] [Table 2]

[0079] [Table 3]

[0080] As shown in Tables 1 to 3, it can be seen that the characteristics of Examples 1 to 10 are superior to those of Comparative Examples 1 to 5. Specifically, it can be seen that when a boron compound is used alone, and in Comparative Examples 2 and 3 which contain a large amount of boron compound, serious film peeling occurs and the magnetic characteristics are inferior. It can also be seen that in Comparative Examples 1, 4 and 5 which do not contain a boron compound or contain an excessively small amount of boron compound, cracks occur on the surface and the insulation and magnetic characteristics are also inferior to those of the Examples. Among the examples, it can be seen that when a ceramic layer is additionally included, the insulating properties are further improved. It can be seen that, among the examples, when no metal hydroxide is included, the iron loss characteristics are relatively poor, and this is due to the effect of the metal hydroxide suppressing the decomposition of the ALN system.

[0081] Fig. 2 is a scanning electron microscope (SEM) photograph of the coating of the grain-oriented electrical steel sheet produced in Example 9. It can be seen from this that a uniform coating without defects was formed. Fig. 3 is a scanning electron microscope (SEM) photograph of the coating of the grain-oriented electrical steel sheet produced in Comparative Example 2. From this, it can be confirmed that multiple cracks have been formed, which have resulted in deep surface peeling. FIG. 4 shows the results of an EPMA (Electron Probe Micro-Analyzer) analysis of the B element of the coating of the grain-oriented electrical steel sheet produced in Example 3. FIG. 5 shows the results of an EPMA (Electron Probe Micro-Analyzer) analysis of the B element of the coating of the grain-oriented electrical steel sheet produced in Example 6. FIG. 6 shows the results of an EPMA (Electron Probe Micro-Analyzer) analysis of the B element of the coating of the grain-oriented electrical steel sheet produced in Comparative Example 3. As can be seen from Figs. 4 to 6, it can be seen that boron aggregates are appropriately formed in the coating of the grain-oriented electrical steel sheet produced in the examples.

[0082] Experimental example 2: Evaluation of magnetic properties, drip rate and noise characteristics of a 1000kVA transformer Example 11 A slab was prepared containing 3.3 wt% silicon (Si), 0.03 wt% aluminum (Al), 0.03 wt% antimony (Sb), 0.05 wt% tin (Sn), 0.02 wt% nickel (Ni), 0.05 wt% carbon (C), 30 ppm nitrogen (N), and the remainder being Fe and its unavoidable impurities. The slab was heated at 1150°C for 220 minutes and then hot rolled to a thickness of 2.3 mm to produce a hot-rolled sheet.

[0083] The hot-rolled sheet was heated to 1120°C, maintained at 920°C for 95 seconds, quenched in water, pickled, and then cold-rolled to a thickness of 0.23 mm to produce a cold-rolled sheet. The cold-rolled sheet was placed in a furnace maintained at 850°C and then maintained in a mixed atmosphere of 74 vol% hydrogen, 25 vol% nitrogen, and 1 vol% dry ammonia gas for 180 seconds, whereby decarburization and primary recrystallization annealing were simultaneously performed to produce a primary recrystallization annealed steel sheet. The annealing separator composition was prepared by mixing 38 wt% of boron compound (MgB2), 3.8 wt% of nickel hydroxide, 5 wt% of titanium oxide, 35 wt% of Sb2(SO4) and the remainder magnesium oxide (MgO) with distilled water to prepare a slurry. The slurry was applied to the steel sheet that had been subjected to the first recrystallization annealing using a roll, and then the steel sheet was subjected to the second recrystallization annealing. During secondary recrystallization annealing, the primary crack temperature was 700°C, the secondary crack temperature was 1200°C, and the temperature range in the heating section was 15°C / hr. In addition, up to 1200°C, a mixed gas atmosphere of 50 volume % nitrogen and 50 volume % hydrogen was used, and after reaching 1200°C, a 100 volume % hydrogen gas atmosphere was used for 20 hours, followed by furnace cooling.

[0084] Then, a ceramic layer-forming composition containing 45% by weight of colloidal silica, 45% by weight of aluminum diphosphate, 5% by weight of chromium oxide, and 5% by weight of nickel hydroxide was mixed and applied to the surface of the final annealed sheet at a rate of 4.5 g / m 2 After coating as shown above, the material was dried in a drying oven set at 860°C for 120 seconds, and then laser domain refining was performed. A 1000kVA transformer was manufactured and evaluated under 60Hz conditions according to the designed magnetic flux density. The results are shown in Table 4 below.

[0085] Comparative Example 6 The same procedure as in Example 11 was carried out, but using an annealing separator composition containing 90% by weight of magnesium oxide, 5% by weight of titanium oxide and 35% by weight of Sb2(SO4). The drip rate was measured using a measuring device according to the international standard JIS C2550. After stacking electrical steel sheet specimens in multiple layers, a uniform pressure of 1 MPa was applied to the surface, and the height of the four sides of the specimen was precisely measured, and the actual weight ratio due to the stacking of electrical steel sheets was divided by the theoretical weight to measure the drip rate. The noise evaluation method is the same as the international standard IEC61672-1, but instead of negative pressure, vibration data of the electrical steel plate is obtained and evaluated in terms of noise equivalent value [dBA]. The vibration of the electrical steel plate is measured by using a laser Doppler method to measure the vibration pattern over time in a non-contact manner when a magnetic field with a frequency of 60 Hz is magnetized with AC up to 1.7 Tesla.

[0086] [Table 4]

[0087] As shown in Table 4, it can be confirmed that the characteristics of Example 11 are significantly superior to those of Comparative Example 6.

[0088] The present invention is not limited to the examples, and can be manufactured in various different forms, and a person having ordinary skill in the art to which the present invention pertains can understand that the present invention can be embodied in other specific forms without changing the technical idea or essential characteristics of the present invention. Therefore, it should be understood that the above-described examples are illustrative in all respects and not limiting. [Explanation of symbols]

[0089] 10 Grain-oriented electrical steel substrate 20. Membrane 30 Ceramic Layer 100 Grain-oriented electrical steel sheet

Claims

1. Based on 100% total solids by weight 25 to 80 weight percent boron, and An annealing separator composition for grain-oriented electrical steel sheet, comprising at least one of magnesium oxide and magnesium hydroxide as the balance.

2. The boron compound is BBr 3 , BCl 3 , B.F., B.F. 3 , B.I. 3 , BN, B(NO 3 ) 3 , B(OH) 3 , B.P., B.P.O. 4 , B 2 F 4 , B 2 C 4 , B 2 H 6 , B.H. 3 N.H. 3 , B 2 O.B. 2 O 3 , B 2 S 3 , B 4 C, B 6 O.B. 5 H 9 , B 5 H 11 , B 6 H 10 , B 6 H 12 , LiBH 4 , H 3 B.O. 3 , Na 2 B 4 O 7 , H 2 B 4 O 7 , B 2 O 3 , B 2 O.B. 2 C, MgB 2 , H[B(OH) 4 ], H[BF(OH) 3 ], H[BF 2 (OH) 2 ], H[BF 3 (OH)] and H[BF 4 2. The annealing separator composition for grain-oriented electrical steel sheet according to claim 1, further comprising at least one of the following:

3. The annealing separator composition for grain-oriented electrical steel sheet according to claim 1, further comprising 0.1 to 20% by weight of a metal hydroxide.

4. The metal hydroxide is Ni(OH). 2 , Co(OH) 2 , Cu(OH) 2 , Sr(OH) 2 , Ba(OH) 2 , Pd(OH) 2 , In(OH) 3 , Bi(OH) 3 The annealing separator composition for grain-oriented electrical steel sheet according to claim 3, further comprising one or more of the following:

5. The annealing separator composition for grain-oriented electrical steel sheet according to claim 1, further comprising 0.5 to 10% by weight of a ceramic powder.

6. The ceramic powder is made of MnO, Al 2 O 3 , SiO 2 , TiO 2 The annealing separator composition for grain-oriented electrical steel sheet according to claim 5, further comprising at least one of ZrO and ZrO.

7. Sb 2 (SO 4 ) 3 , SrSO 4 and BaSO 4 The annealing separator composition for grain-oriented electrical steel sheet according to claim 1, further comprising 1 to 10% by weight of one or more of the following:

8. Grain-oriented electrical steel substrate, and The coating is located on one or both sides of the grain-oriented electrical steel sheet substrate and includes a coating containing boron and forsterite, The coating contains boron agglomerates, and the average particle size of the boron agglomerates is 1 to 500 nm.

9. The grain-oriented electrical steel sheet according to claim 8, characterized in that the boron aggregates are contained in an amount of 1 to 45 area % based on the total area of ​​the coating.

10. The grain-oriented electrical steel sheet according to claim 8, characterized in that the coating contains 1 to 40 wt% B, 10 to 70 wt% Mg, 3 to 70 wt% Si, 10 to 90 wt% O, and Fe as the balance.

11. The grain oriented electrical steel sheet of claim 8 further comprising a ceramic layer located on the coating.

12. The grain oriented electrical steel sheet of claim 11 , wherein the ceramic layer comprises a ceramic powder and a metal phosphate.

13. The ceramic powder is Al 2 O 3 , SiO 2 , TiO 2 , ZrO 2 , Al 2 O 3 TiO 2 , Y 2 O 3 , 9Al 2 O 3 ・2B 2 O 3 , BN, CrN, BaTiO 3 13. The grain-oriented electrical steel sheet according to claim 12, further comprising at least one selected from the group consisting of SiC, SiC and TiC.

14. Preparing a steel slab; hot rolling the steel slab to produce a hot rolled sheet; cold rolling the hot-rolled sheet to produce a cold-rolled sheet; subjecting the cold-rolled sheet to a primary recrystallization annealing; Applying an annealing separator to the surface of the steel sheet that has been subjected to the first recrystallization annealing; and subjecting the steel sheet coated with the annealing separator to secondary recrystallization annealing; The annealing separator contains, based on 100% by weight of a total solid content, 25 to 80% by weight of a boron compound and the remainder being one or more of magnesium oxide and magnesium hydroxide.

15. The method for producing a grain-oriented electrical steel sheet according to claim 14, further comprising the step of forming a ceramic layer on the coating containing boron and forsterite after the step of secondary recrystallization annealing.

16. The step of forming the ceramic layer comprises: The method for producing a grain-oriented electrical steel sheet according to claim 14, further comprising spraying a ceramic powder onto the coating to form a ceramic layer.

Citation Information

Patent Citations

  • Grain-oriented electrical steel sheet and method for manufacturing the same

    JP2019508577A

  • Annealing separator composition for grain-oriented electrical steel sheet, grain-oriented electrical steel sheet, and method for producing grain-oriented electrical steel sheet

    JP2020511591A

  • Method for producing directional electromagnetic steel sheet and directional electromagnetic steel sheet, and annealing separation agent

    JP2021123767A

  • Anti-oxidant, anti-bacterial, anti-hypertension, or anti-gout composition comprising extract of Sambucus sieboldiana var. pendula as an active ingredient

    KR1020220169298A

  • Grain-oriented electrical steel sheet

    WO2019065645A1